Islamic Boarding School-Based School Management (Exploratory Study of Academic and Non-Academic Achievement Development at SMPIT Nurul Islam Tengaran) - Nisa, Fakhrun; Saputra, Budiyono (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to: (1) describe Islamic boarding school-based school management in developing students' academic and non-academic achievements. (2) describe the principal's strategy in developing students' academic and non-academic achievements, (3) describe the success of Islamic boarding school-based school management in developing students' academic and non-academic achievements at SMPIT Nurul Islam Tengaran.This research uses a descriptive qualitative approach. The research subjects were the principal, teachers and students of SMPIT Nurul Islam Tengaran. The data collection techniques used were interviews, observation and documentation. Data analysis was carried out in the following stages: obtaining data, data reduction, data presentation, conclusions and verification. The research results show that; (1) Islamic boarding school-based school management implemented by SMPIT Nurul Islam to develop students' academic and non-academic achievements has shown that the system is working well. (2) The strategy carried out by the school principal is realized through several activities, namely by providing tutoring to students, developing students' talents and potential through student activities, developing student learning activities, upgrading competition coaches, and providing motivation to students. (3) The success of Islamic boarding school-based school management in developing the academic and non-academic achievements of SMPIT Nurul Islam Tengaran students is due to the increase in the number of students and the many types of achievements achieved by the school.